Projects of classroom in the knowledge management in the national university Hermilio Valdizán, Huánuco, Peru - Bustamante P., Nicéforo (2017)
The distinctive features of valencian university didactics are the transmission of information with little knowledge management by the student and the teacher. The objective was to renew the didactics through classroom projects in the management of knowledge. The methodology consisted of the practice of the training partner, focused on personalized work, research action and collaborative work. The results are the assessment of metacognition, the importance of individual talent, and the socialization of knowledge in learning brigades. We conclude that the classroom project in the classroom is a didactic strategy that allows for discerning levels of learning, from individual work, learning in brigades and socialization of knowledge.